Measurement of the Λ0b lifetime and mass in the ATLAS experiment - Alonso, Francisco (2013)
A measurement of the Λ0b lifetime and mass in the decay channel Λ0b →J/ψ(μ+μ¯)Λ0(pπ¯) is presented. The analysis uses a signal sample of about 2200 Λ0b and Λ¯0b decays that are reconstructed in 4.9 fb-1 of ATLAS pp collision data collected in 2011 at the LHC center-of-mass energy of 7 TeV. A simultaneous mass and decay time maximum likelihood fit is used to extract the Λ0b lifetime and mass. They are measured to be τΛb=1.449±0.036(stat) ±0.017(syst) ps and mΛb=5619.7±0. 7(stat)±1.1(syst) MeV.